Pengaruh Brand Ambasador dan Citra Merk terhadap Minat Beli Barenbliss (Studi pada Komunitas X Oh My Beauty Bank) - Siswanto, Victorie Gracia; Haryono, Cosmas Gatot (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research examines the influence of Brand Ambassadors and Brand Image on Purchase Intention of Barenbliss products among members of the X Oh My Beauty Bank community. In the competitive cosmetics industry, companies need effective marketing strategies to stand out. This study employed quantitative research with a deductive approach, utilizing purposive sampling to collect data from 400 respondents who are members of the X Oh My Beauty Bank community, aged at least 18 years, and have used Barenbliss products for over six months. Path analysis revealed that both brand ambassadors and brand image significantly influence purchase intention, both individually and simultaneously. Brand ambassadors, measured through attractiveness, trustworthiness, and expertise, create emotional connections with consumers, while brand image, assessed through recognition, reputation, affinity, and domain, strengthens consumer perception of the brand. The findings suggest that integrating these strategies creates a comprehensive approach to enhance consumer purchase intention in the dynamic cosmetics market.